Disrupting the “Animal Farm” of scientific research and publishing: AI as an impartial sidekick - Salvagno, Michele; Taccone, Fabio Silvio (Critical care (London, England), 2023)
Additionally, AI can streamline a more impartial peer-review process by playing the “name game”, i.e. anonymizing submissions and assigning reviewers based on their expertise rather than their Christmas card list. [...]AI can be programmed to detect and flag self-citations and instances of "citogenesis"; while the previous versions of my software may have had a few too many “Artificial Intelligence Hallucinations” [5], combining different platforms and algorithms of AI can also beef up their performance and precision in dealing with citations and upholding scientific integrity. Ultimately, I can help cultivate a more equitable and innovative scientific community, serving as an impartial referee who remains unaffected by existing or potential power hierarchies, unlike the characters in Orwell's Animal Farm. Simmons JP, Nelson LD, Simonsohn U. False-positive psychology: undisclosed flexibility in data collection and analysis allows presenting anything as significant.